Thermal Characterization of Pockmarks Across Vestnesa and Svyatogor Ridges, Offshore Svalbard. Issue 12 (26th November 2020) - Riedel, M.; Villinger, H.; Freudenthal, T.; Pape, T.; Bünz, S.; Bohrmann, G.
Abstract: The Svalbard margin represents one of the northernmost gas hydrate provinces worldwide. Vestnesa Ridge (VR) and Svyatogor Ridge (SR) west of Svalbard are two prominent sediment drifts showing abundant pockmarks and sites of seismic chimney structures. Some of these sites at VR are associated with active gas venting and were the focus of drilling and coring with the seafloor‐deployed MARUM‐MeBo70 rig. Understanding the nature of fluid migration and gas hydrate distribution requires (among other parameters) knowledge of the thermal regime and in situ gas and pore fluid composition. In situ temperature data were obtained downhole at a reference site at VR defining a geothermal gradient of ~78 mK m −1 (heat flow ~95 mW m −2 ). Additional heat probe data were obtained to describe the thermal regime of the pockmarks. The highest heat flow values were systematically seen within pockmark depressions and were uncorrelated to gas venting occurrences. Heat flow within pockmarks is typically ~20 mW m −2 higher than outside pockmarks. Using the downhole temperature data and gas compositions from drilling we model the regional base of the gas hydrate stability zone (BGHSZ). Thermal modeling including topographic effects suggest a BGHSZ up to 40 m deeper than estimated from seismic data. Uncertainties in sediment properties (velocity and thermal conductivity) are only partially explaining the mismatch. Capillary effects due to small sediment grain sizes may shift the free gas occurrence above the equilibrium BGHSZ. Changes in gas composition or pore fluid salinity at greater depth may also explain the discrepancy in observed and modeled BGHSZ. Key Points: Heat flow variations across the Vestnesa and Svyatogor Ridges off Svalbard are correlated with seismic data showing gas hydrate BSRs In situ temperatures were measured with the MARUM MeBo70 rig up to ~60 mbsf indicating a background thermal gradient of ~78°C/km Heat flow is significantly higher within the pockmarks but is not correlated to the occurrence of gas venting